Determinants of Financial Hedging Strategies among Commodity Producer Firms in Latin America - Giraldo, Carlos; Giraldo, Iader; Huertas, Cristian; Sanchez, Juan Camilo (International Journal of Energy Economics and Policy, 2026)
This study investigates the determinants of hedging practices among commodity-producing companies in Latin America. The economic significance of the extractive sector in the region makes understanding firms’ hedging decisions and their impact on firm value highly relevant. The findings reveal several key insights. Firm size, leverage, and commodity prices are important factors consistent with prior research. Additionally, the region’s exchange rate exposure means that firms’ acquisition of US dollar-denominated debt is a significant determinant of their hedging activities, as well as the firms’ access to the international markets. Notably, the type of ownership also significantly impacts hedging, as state-owned firms are more likely to hedge to reduce volatility in their revenues for the case of oil-firms. In contrast to the limited research on Latin American extractive firms, an extensive literature has explored hedging strategies in developed countries’ extractive companies. This study aims to address the gap by investigating the determinants of hedging practices among commodity-producing companies in Latin America and their impact on firms’ value.